2016
DOI: 10.1039/c6en00361c
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of chronic toxicity to Daphnia magna induced by graphene suspended in a water column

Abstract: The mechanism of chronic toxicity induced by graphene to Daphnia magna compared with that of C60, SWCNT, and MWCNT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
1
14
0
2
Order By: Relevance
“…The actual exposure concentration of GNMs in the assessed ecotoxicology studies was confirmed in 6 studies: Tang et al [40] (in suspension/test media); Hu et al [41] (in algae cells); Guo et al [38] and Lu et al [42] (in aqueous-phase and in Daphnia); Feng et al [43] (by release of 14 CO 2, in suspension and in Daphnia); and Fan et al [44] (in Daphnia). Quantification of graphene was assessed in solution by measuring the aqueousphase radioactivity for 14 C-labeled materials [38].…”
Section: Derivation Of Water Quality Guideline Values For Gnmsmentioning
confidence: 80%
See 3 more Smart Citations
“…The actual exposure concentration of GNMs in the assessed ecotoxicology studies was confirmed in 6 studies: Tang et al [40] (in suspension/test media); Hu et al [41] (in algae cells); Guo et al [38] and Lu et al [42] (in aqueous-phase and in Daphnia); Feng et al [43] (by release of 14 CO 2, in suspension and in Daphnia); and Fan et al [44] (in Daphnia). Quantification of graphene was assessed in solution by measuring the aqueousphase radioactivity for 14 C-labeled materials [38].…”
Section: Derivation Of Water Quality Guideline Values For Gnmsmentioning
confidence: 80%
“…The studies with pristine graphene did not include protozoa, fungi, and ciliates. However, a study of pristine graphene effects at low concentrations (0.1 mg/L) on invertebrates ( D. magna ) recorded a stimulation of growth . This observation may be related to hormesis or stress response .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS氧化 生物体内的不饱和脂肪酸而生成的脂质过氧化物产 物丙二醛(MDA), 可用于评价生物体氧化损伤的程 度 [19] . 因此, 本研究选取5种石墨烯及其表面官能化 [20,21] , 本研究选择0~16 mg/L石墨烯及其表面官…”
Section: 生物体内抗氧化防御系统维持着Ros的动态平 衡 抗氧化酶Sod Cat及抗氧化剂谷胱甘肽(gsh)unclassified